2017
DOI: 10.1016/j.carbpol.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Wheat straw hemicelluloses added with cellulose nanocrystals and citric acid. Effect on film physical properties

Abstract: Wheat straw has been used as a source of hemicelluloses (WSH) and cellulose nanocrystals (CNC) for the elaboration of biodegradable films. Different films have been formed by using WSH as a matrix and different contents of CNC and citric acid. The predominant hemicelluloses were arabinoxylans. CNC reinforced the films, improving tensile strength and modulus, water resistance and water vapor barrier. Citric acid, on the other hand, presented concomitant plasticizing and crosslinking effects (the latter also evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…e peak appearance shows Journal of Chemistry a change in the chemical structure after the addition of citric acid, indicating that there was some cross-linking that may have taken place between citric acid and the ber. e decrease in intensity was observed in the band at 1626 cm −1 (absorbed water in the lms) when citric acid was present, probably because some of the hydrophilic groups were involved in the cross-linking, and thus, the lms absorbed less water [25]. is is consistent with the result of tensile strength and the WVP.…”
Section: Ftir Analysis Of Eaep Residuesupporting
confidence: 84%
“…e peak appearance shows Journal of Chemistry a change in the chemical structure after the addition of citric acid, indicating that there was some cross-linking that may have taken place between citric acid and the ber. e decrease in intensity was observed in the band at 1626 cm −1 (absorbed water in the lms) when citric acid was present, probably because some of the hydrophilic groups were involved in the cross-linking, and thus, the lms absorbed less water [25]. is is consistent with the result of tensile strength and the WVP.…”
Section: Ftir Analysis Of Eaep Residuesupporting
confidence: 84%
“…Table 6 shows examples of NCCs used as fillers in polymeric matrices. Cassava starch Solution casting Food packaging [62] Sugar palm starch Solution casting Food packaging [115] Wheat starch Solution casting Food packaging [87] Tuber native potato Solution casting Packaging [116] Cereal corn Solution casting Packaging [116] Legume pea Solution casting Packaging [116] Waterborne acrylate Solution mixing Corrosion protection [79] Wheat straw hemicelluloses Water hyacinth fiber NFC Yam bean starch [127] Wheat straw NFC No attempts were made with composites [29] Wheat straw NCC Wheat straw hemicelluloses [96] Wood pulp NFC/ NCC PVA (10 wt% filler), PLA (5 wt% filler) [120,128] Cassava bagasse NCC Cassava starch [62] Ramie NCC Wheat starch [87] Phormium tenax (harakeke) fiber NCC PVA [83] Flax fiber NCC PVA [83] Potato peel fiber NCC Starch [84] Table 5. Different nanocellulose sources of reinforcement fillers in polymer matrices.…”
Section: Applications Of Nanocrystalline Cellulose From Agro-waste Fimentioning
confidence: 99%
“…It was found that cellulose nanocrystalline (CNC) is capable of overcoming this disadvantage. Pereira and co-workers [ 39 ] added CNC to wheat straw hemicellulose for film preparation, and found that the addition of CNC effectively improved the tensile strength, tensile modulus, and moisture resistance of the blend film ( Table 5 ). A possible explanation is that with the addition of CNC, a large number of hydrogen bond networks are generated in the composite film [ 40 ].…”
Section: Modification Of Hemicellulosementioning
confidence: 99%